How Many Congregations Are There? Updating a Survey-Based Estimate. - Brauer, Simon G. (Journal for the Scientific Study of Religion (John Wiley & Sons, Inc.), 2017)
Researchers have attempted to estimate the number of congregations in the United States using counts provided by denominations, existing media (newspapers, phone books, websites, etc.), and calculations using congregational surveys. Hadaway and Marler (2005) took the third approach, basing their estimate on the 1998 National Congregations Study (NCS), a representative sample of U.S. congregations, and select official denominational statistics. Since publishing their estimate of 331,000 congregations in 1998, two subsequent waves of the NCS have been conducted. Using the same approach, I estimate the number of congregations in 1998, 2006, and 2012. I conclude that congregations probably became more numerous, likely due to growth among nondenominational Protestants and the extraordinarily low death rate of congregations. But I also consider alternative interpretations of the data.